Information stickiness on general equilibrium and endogenous cycles - Orlando Gomes (Economics: The Open-Access, Open-Assessment E-Journal, 2013)
Traditionally, observed fluctuations in aggregate economic time series have been mainly modeled as being the result of exogenous disturbances. A better understanding of macroeconomic phenomena, however, surely requires looking directly at the relations between variables that may trigger endogenous nonlinearities. Several attempts to justify endogenous business cycles have appeared in the literature in the last few years, involving many types of different settings. This paper intends to contribute to such literature by investigating how we can modify the well-known information stickiness macro model, through the introduction of a couple of reasonable new assumptions, in order to trigger the emergence of endogenous fluctuations.
Keywords: E32; E10; C61; C62; 330; endogenous cycles; information stickiness; macroeconomic fluctuations; general equilibrium; periodicity and chaos; Konjunkturtheorie; Information; Makroökonomischer Einfluss; Volatilität; Theorie